PRODUCTION OF SEMI REFINE CARRAGEENAN (SRC) FROM FRESH Kappaphycus alvarezii USING MODIFIED TECHNIQUE WITH MINIMUM USE OF FUEL - Jamal Basmal; Diah Ikasari (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
Semi refine carrageenan (SRC) is generally produced by cooking dried Kappaphycus alvareziiinto hot alkali solution at temperature of 80ºC for 2 hours. However, the temperature fluctuationduring the production process affects to the increase of production cost and the reduction of theyield as well as the decrease of SRC quality. The improvement of this process can be achieved bysoaking immediately fresh K. alvarezii into cold alkali solution, called cold alkali technique. Inorder to obtain its optimum condition, modification of SRC production process using cold alkalitechnique had been conducted. Fresh K. alvarezii was soaked in 8% KOH at room temperaturefor 10, 20, 30, 40, and 50 days. The alkalinized K. alvarezii was then washed with fresh water untilpH reached to 7 – 8, chopped to the size of 3 – 5 mm and then dried under sun light. The SRCbeing produced was then evaluated for its quality. The result showed that the quality of SRC fromfresh seaweed K. alvarezii was affected by soaking time. The highest quality of SRC was obtainedby soaking K. alvarezii with 8% KOH solution for 50 days. This was indicated by the ester sulphatecontent of 6.74 %, water gel strength of 746 g/cm2, and moisture content of 11.73 %.